Fracture and Failure of Natural Building Stones Applications in the Restoration of Ancient Monuments - Kourkoulis, Stavros K. (Springer Netherlands : Imprint: Springer, 2006)
The fracture and failure of natural building stones has been for many years the concern of the engineering community and particularly the c- munity of scientists working for the restoration and conservation of stone monuments. The need to protect the authentic stone and the requirement for reversibility of the interventions rendered the in-depth knowledge of the mechanical behaviour of both the authentic material and its substitutes - dispensable. This book contains 36 papers presented at the Symposium on "Fracture and Failure of Natural Building Stones" which was organized in the frame of the "16th European Conference on Fracture (ECF16)". The Conference took place in Alexandroupolis, Hellas on July 3-7, 2006. To my best kn- ledge this is the first time that a special Symposium of a European C- ference on Fracture is devoted exclusively to the study of the fracture and failure of building stones. The book consists of invited papers written by leading experts in the field. It contains original contributions concerning the latest developments in the fracture and failure of the natural building stones and their application in the restoration of ancient monuments. It covers a wide range of subjects - cluding purely mechanical aspects, physico-chemical approaches, appli- tions and case studies. The papers are arranged in two parts with a total of nine chapters. Part I is devoted to purely mechanical and structural aspects and applications, while Part II is devoted to the physico-chemical and environmental aspects including thermal effects.